Pattern of Serum Vitamin D in Hospitalised Patients: A Retrospective Study - Chhetri, Niru; Chhetri, Ajit; Mukherjee, Arati; Bhattacharya, Gora Chand; Sen, Sandip; Kumar, Abhay (International Journal of Medical Research and Review, 2016)
Background: To find out the prevalence of vitamin D deficiency in patients hospitalised in two tertiary care centres for various ailments in Eastern Bihar and North Bengal. Methods: Hospitalised patients in MGM Medical College, Kishanganj, Bihar and Medical North Bengal Clinic, Siliguri, West Bengal (Jan 2014 to Dec 2014) who underwent blood sampling for vitamin D estimation in their work up for various ailments were included in the study. Result: Out of 108 patients, 65 were female and 43 were male in the age group ranging from 1 month to 85 years. Maximum number of patients was in the age group of 41 to 60 years. Seventy two percent patients had low vitamin D levels with 54.63% having frank deficiency and 17.59% had insufficient levels. Diabetes mellitus and/or hypertension were the most common diseases associated with hypovitaminosis D followed by diseases of respiratory system. Conclusion: Vitamin D deficiency was seen in 72 % of the subjects with female preponderance. No age was spared as the age of the subjects ranged from 1 month to 85 years with majority in the 41 to 60 years age group. Among subjects with hypovitaminosis D, diabetes mellitus and /or hypertension were the most commonly encountered diseases.